2021
DOI: 10.3389/fimmu.2020.604055
|View full text |Cite
|
Sign up to set email alerts
|

IL-33/Vitamin D Crosstalk in Psoriasis-Associated Osteoporosis

Abstract: Patients with psoriasis (Pso) and, in particular, psoriatic arthritis (PsoA) have an increased risk of developing osteoporosis (OP). It has been shown that OP is among the more common pathologies associated with Pso, mainly due to the well-known osteopenizing conditions coexisting in these patients. Pso and OP share common risk factors, such as vitamin D deficiency and chronic inflammation. Interestingly, the interleukin (IL)-33/ST2 axis, together with vitamin D, is closely related to both Pso and OP. Vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 130 publications
0
14
0
Order By: Relevance
“…5 Journal of Immunology Research the production of Th2 cytokines IL-4 and IL-10 was promoted by IL-33 [18], and Th2 immune response was described to influence the pathogenesis of respiratory syncytial virus (RSV) acute bronchiolitis [19]. Firstly, the expression of IL-33 in serum of acute bronchiolitis infants infected by RSV was examined by ELISA assay; we found that IL-33 concentrations in AVB infants were significantly increased compared to normal subjects (Figure 1(a)).…”
Section: Resultsmentioning
confidence: 99%
“…5 Journal of Immunology Research the production of Th2 cytokines IL-4 and IL-10 was promoted by IL-33 [18], and Th2 immune response was described to influence the pathogenesis of respiratory syncytial virus (RSV) acute bronchiolitis [19]. Firstly, the expression of IL-33 in serum of acute bronchiolitis infants infected by RSV was examined by ELISA assay; we found that IL-33 concentrations in AVB infants were significantly increased compared to normal subjects (Figure 1(a)).…”
Section: Resultsmentioning
confidence: 99%
“…1,25(OH) 2 D is shown to abrogate the osteoclastogenic potential and proinflammatory cytokine secretion capacity of immune cells of patients with psoriasis and PsA [ 92 , 93 , 94 ]. This could explain the observation that serum 25(OH)D was inversely correlated with presence of PsA [ 95 ], as well as plasma C-reactive protein level among patients with PsA [ 96 ].…”
Section: Evidence On Vitamin D For Prevention and Treatment Of Rheumatic Diseasesmentioning
confidence: 99%
“…Vitamin D, in fact, is important in the maintenance of bone health through the regulation of serum calcium homeostasis. The lack of vitamin D increases bone resorption in order to maintain the right serum calcium levels, making up for the lack of calcium reabsorbed by the gut induced by vitamin D deficiency [ 112 ].…”
Section: Discussionmentioning
confidence: 99%